Copper-mediated nucleophilic 18F-radiolabelling of (hetero)arenes for applications in positron emission tomography - Taylor, N (2017)
This thesis focuses on the development of a novel nucleophilic 18F-fluorination of (hetero)arenes and of a rapid screening experiment to facilitate the application of this reaction to complex heterocyclic targets of medicinal importance. Chapter 1 introduces the use of molecules labelled with fluorine-18 as tracers in positron emission tomography and reviews methods for the preparation of [18F]fluoroarenes published prior to the start of the work in this thesis. Chapter 2 describes the development of a novel method for the preparation of electronically-diverse [18F]fluoroarenes from aryl boronic esters and [18F]fluoride, mediated by a copper complex. Application of this 18F-fluorodeboronation to electron-rich radiotracers is demonstrated. Methods for the preparation of [18F]fluoroarenes published after the start of the work in this thesis are reviewed. Chapter 3 outlines a rapid screening experiment for assessing the tolerance of the 18F-fluorodeboronation towards heterocycles, and the use of this method to guide the retro-radiosynthesis of heterocycle-rich, medicinally relevant molecules. Chapter 4 contains synthetic procedures and characterisation data for compounds in Chapters 2 and 3.